2012
DOI: 10.1016/j.jcin.2012.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Early, Late, and Very Late Stent Thrombosis After Primary Percutaneous Coronary Intervention With Bare-Metal and Drug-Eluting Stents for ST-Segment Elevation Myocardial Infarction

Abstract: Stent thrombosis after primary percutaneous coronary intervention is relatively frequent and continues to increase out to 5 years. New strategies are needed to prevent ST in STEMI patients, and targeted therapies are needed in patients identified at highest risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
2
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 23 publications
2
36
2
1
Order By: Relevance
“…We demonstrated that ACS, longer stent length, and lack of CCB use were associated with an increased risk of ST after DES implantation within 1 year in [5]. If subjects were limited to those with ACS who underwent PCI, this tendency was more prominent [14]. Therefore, there are limited data to predict ST occurrence in Japan.…”
Section: Discussionmentioning
confidence: 96%
“…We demonstrated that ACS, longer stent length, and lack of CCB use were associated with an increased risk of ST after DES implantation within 1 year in [5]. If subjects were limited to those with ACS who underwent PCI, this tendency was more prominent [14]. Therefore, there are limited data to predict ST occurrence in Japan.…”
Section: Discussionmentioning
confidence: 96%
“…No significant difference was observed between BMS and DES in terms of the incidence of death and recurrent AMI [1,2,6,[10][11][12]. On the other hand, accumulating data began to show a higher risk of stent thrombosis in those treated with DES over a 1-year follow-up period [3,6,9]. Kalesan et al [8] demonstrated in meta-analysis that 1 year after AMI treatment, very late SO is significantly more likely to occur in patients receiving DES than in those with BMS placement.…”
Section: Discussionmentioning
confidence: 99%
“…Retrospective registries with intravascular ultrasound (IVUS) imaging in patients with BMS-ST, report of stent underexpansion as the cause of early ST in more than every second case (18). Indeed, severe stent underexpansion is more common in subjects with early ST, suggesting that early and late ST have different underlying mechanisms (4,7,19). Underexpansion and acute malapposition occurs as a result of inadequate stent expansion during index PCI.…”
Section: Uncovered Struts Underexpansion Malapposition and Neoathermentioning
confidence: 99%